Implementation Framework National Institute of Standards and Technology (Nist) Evidence Digital In The Forensic Process Social Media - Radika Muzdalifa Abubakar; Muhammad Sabri Ahmad; Syarifuddin N. Kapita; Ahmad Fuad (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Many people carry out social media activities which are not only positive activities but also activities that have a negative impact, such as crimes in cyberspace. especially forensics mobile in assisting the resolution of crime cases through social media Instagram with media access smartphone. The biggest problem in the data retrieval process is that the perpetrator deletes or tries to eliminate digital evidence on a smartphone so this research aims to implement the framework National Institute of Standards and Technology to investigate data forensic evidence on social media Instagram accessed via smartphone Android by using tools mobile Edit forensic in data extraction on a smartphone with workflow stages collection, - reporting. This study uses a conversation scenario on the Instagram feature direct message (DM) with conditions including deleting data on the Instagram application. The method used in handling cybercrime with media evidence smartphones is the method National Institute of Standards and Technology (NIST). The results of this study are in collecting data in the form of 25 conversations (chat), 206 images, 86 videos, 5 audio, and 4 call logs on smartphones. However tools MOBILEdit Forensic in returning digital evidence are unable to recover conversations and call logs as a whole.